Numerical and Experimental Heat Transfer Characterisation of Paraffin Wax Material with Different Heated Tube Arrangements - Suditama, (2008)
The aim of this study is to obtain the heat transfer characteristics of the heated tube inline and staggered arranged immersed in the thermal energy storage material (paraffin wax) as phase change material (PCM). The information about thermo-physical properties of phase change thermal storage material and heat transfer characteristic is very important for designing of thermal energy storage system. The Differential Scanning Calorymetery (DSC), density meter, thermal conductivity meter, and viscometer are used for measuring the thermo-physical properties of thermal energy storage material (paraffin wax). Analysis of the heat transfer characteristics of heated tube inline and staggered arrangement immersed in the thermal energy storage material by experimental and numerical were used. These results would be helpful in developing analyses and in their verification to design thermal energy storage system. This study also presents an efficient and adequate of numerical technique for solving transient heat transfer problem of melting processes and then compare to the experimental result. The proposed technique comprises between the specific heat capacity and conduction/convection is heat transfer modes for solved the problem by a finite difference scheme. The temporal heat storage and the movement rate of solid-liquid interface in paraffin wax as phases change material (PCM) heated tube inline and staggered arrangement are studied. Numerical scheme is suitable for solving phase change problem with boundary condition of constant heat flux. The result scheme is efficient and adequate. The numerical results agree fairly well with the experimental results, which show that the model is accurate enough to predict the solid PCM melting rate and the time needed to the melt of the solid PCM. The model also can be used to optimize the design and operation of thermal energy storage system with PCM outside the inline and staggered heated tube arrangement.